Безпека здоров’я та її кримінологічна зацікавленість в умовах воєнних подій нинішнього дня - Сокуренко, В.В.; Sokurenko, V.V.; ORCID: http://orcid.org/0000-0003-4377-982X (Юридичний науковий електронний журнал. - 2022. - № 8. - С. 456-460, 2022)
Висвітлено актуальні питання подолання людських конфліктів, які призводять до військових станів. Надано рекомендації простих богословських і біблійних істин, щоб згладити гострі кути побутових конфліктів та воєнних ситуацій. Наголошено на особливій ролі розроблення військової кримінології, яка здатна відіграти неабияку роль у вирішенні багатьох проблем нинішнього дня. Акцентовано увагу на розвитку військової розвідки та діяльності військово-медичної служби, наповнення їх спеціалістами величини поглядів, справжніми практиками військової медицини. Підкреслено, що професія медика одна із найбільш благородних, яка прирівнюється до Янгола Охоронця, який оберігає людину, державу від протиправних посягань, хвороб суспільсва, які постійно переслідують людину. Головним питанням залишається спасіння людської душі та вироблення подальших наукових досліджень на засадах пріоритету жертовності, служіння ближньому.

The article highlights the current issues of overcoming human conflicts that lead to martial law. Recommendations of simple theological and biblical truths are provided to smooth the sharp edges of domestic conflicts and war situations. Emphasis is placed on the special role of the development of military criminology, which can play a significant role in solving many of today's problems. Special attention is focused on the development of military intelligence and the activities of the military medical service, filling them with specialists of great views, and real practitioners of military medicine. It is emphasized that the medical profession is one of the noblest, which equates to the Guardian Angel, which protects a person, and the state from illegal encroachments, and diseases of a society that constantly haunt a person. The main issue remains the salvation of the human soul and the development of further scientific research based on the priority of sacrifice, and service to one's neighbor. Under the current conditions, the initiative to develop Ukrainian military criminology is quite important, which involves real (routine) daily work in the search for and development of appropriate scientific material in order to optimize the ways and approaches of national science and creativity with its subsequent normative design, as well as the implementation of the best practices in teaching and educational activity, human rights, and law enforcement practice, in the general conceptualization of the relevant material at qualitatively newer levels. Indeed, the reliable defense and industrial potential of the country in the conditions of martial law is needed more than ever. Unfortunately, during the three decades of independence, all science and technology were converted to the humanitarian sphere. At the same time, many of our specialists left the country in search of a better fate abroad. Today, the main task is to preserve the existing scientific and pedagogical potential of the country, because our specialists are in no way inferior to their foreign colleagues, and in many respects, they are superior in knowledge, ingenuity, in particular, the conduct of military operations, as evidenced by recent events, as well as a large number of events for the exchange of experience of the most diverse countries and the real state of affairs.

Освещены актуальные вопросы преодоления человеческих конфликтов, приводящих к военным положениям. Даны рекомендации простых богословских и библейских истин, чтобы сгладить острые углы бытовых конфликтов и военных ситуаций. Отмечена особая роль разработки военной криминологии, которая способна сыграть незаурядную роль в решении многих проблем нынешнего дня. Акцентировано внимание на развитии военной разведки и деятельности военно-медицинской службы, наполнении их специалистами по величине взглядов, настоящими практиками военной медицины. Главным вопросом остается спасение человеческой души и выработка дальнейших научных исследований на основе приоритета жертвенности, служения ближнему.
Health security and its criminology interest in the conditions of today's military events
Сокуренко, В. В. Безпека здоров’я та її кримінологічна зацікавленість в умовах воєнних подій нинішнього дня [Електронний ресурс] / Сокуренко В. В. // Юридичний науковий електронний журнал. - 2022. - № 8. - С. 456-460. - Режим доступу: http://lsej.org.ua/8_2022/104.pdf.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; безпека здоров’я; health safety; безопасность здоровья; воєнна кримінологія; military criminology; военная криминология; військова політика; military policy; военная политика; організаційно-управлінські трансформації; organizational and managerial transformations; организационно-управленческие трансформации; військово-медична служба; military medical service; военно-медицинская служба; воєнний стан; martial law; военное положение